Profile of Language Disorders in Clients of Motor Transcortical Aphasia - Yuli Afmi Ropita Sari; Ilham Akerda Edyyul; Rexsy Taruna; Rahmi Khalida (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
Aphasia is a language disorder that occurs due to an injury to the brain. The classification of aphasia is divided into fluent aphasia and nonfluent aphasia. One of the non-fluent aphasia is transcortical motor aphasia. The characteristics that distinguish Broca's aphasia from other aphasia are disorders in receptive language, difficulty in answering questions, difficulty understanding spoken language, difficulty understanding written language, difficulty writing, accompanied by linguistic symptoms such as ecolalia. The implementation of this research starts from the assessment (observation, interview, and test). The purpose of this research is to find out the language disorder that exists in the client. To see the language disorder that exists in clients, interviews with families and clients are carried out. Then an observation of the client's activity is carried out and a test is carried out to determine the language disorder in the client. The conclusion of this study is that clients experience problems in understanding spoken and written language, clients also have difficulty starting to talk to other people. So the authors recommend that clients get treatment for language disorders.